Mitochondrial DNA lineages of elite Ethiopian athletes - Scott, R. A.; Wilson, R. H.; Goodwin, W. H.; Moran, C; Georgiades, E.; Wolde, B.; Pitsiladis, Y. P. (Comparative Biochemistry and Physiology Part A: Molecular & Integrative Physiology, 2005)
Previous studies have hypothesised that mitochondrial DNA (mtDNA) polymorphisms may influence aerobic performance. The matrilineal inheritance and accumulation of polymorphisms in mtDNA means that mtDNA haplogroups, characterised by key polymorphisms, are often represented at different frequencies in different populations. The present study aimed to compare the mtDNA haplogroup distribution of elite Ethiopian athletes relative to the general Ethiopian population. The haplogroup distribution of 76 endurance athletes (E), members of the Ethiopian national athletics team, was compared to 108 members of the general Ethiopian population (C). DNA was extracted from buccal swabs and haplogroups assigned by sequencing part of the hypervariable sequence (HVS-I), followed by analysis of key coding-region polymorphisms. A high proportion of African `L` haplogroups was found in athletes and controls (C=53%; E=55%). Haplogroup distribution of endurance runners did not differ from that of C (P=0.63). Elite Ethiopian athletes are not a mitochondrially distinct group relative to the Ethiopian population. It appears that environment and, perhaps, polymorphisms in the nuclear genome are more important determinants of Ethiopian running success than mtDNA polymorphisms.